Paleobiogeography of early cretaceous ammonoids - Lehmann, Jens; Ifrim, Christina (Ammonoid paleobiology: from anatomy to ecology, 2015)
Ammonites are often dominant elements of Early Cretaceous marine faunas. Many species are important index fossils, in some cases with worldwide distribution. We review the paleobiogeography for the Early Cretaceous. We recognize three major faunal phases in the distribution of ammonites during that interval. The first phase, directly inherited from the Late Jurassic distribution patterns, extends from the Berriasian to the earliest Barremian, when the faunas of the Boreal Realm are clearly distinguished from the Tethyan Realm. From the late early Barremian to the late Aptian, a second phase is characterized by rather uniform faunas marked by the dominance of Tethyan-derived heteromorphs in the Boreal Realm. The last phase, covering most of the Albian stage, displays a more distinctive differentiation between Boreal and Tethyan faunas. The late Barremian marks the onset of the Austral Realm, originating from faunas that originally evolved in the Indo-Pacific Subrealm of the Tethyan Realm.